The Link between R&D, Innovation and Productivity: Are Micro Firms Different? - Julian Baumann; Alexander S. Kritikos (Institute for the Study of Labor (IZA), 2016)
We analyze the link between R&D, innovation, and productivity in MSMEs with a special focus on micro firms with fewer than 10 employees; usually constituting the majority of firms in industrialized economies. Using the German KfW SME panel, we examine to what extent micro firms are different from other firms in terms of innovativeness. We find that while firms engage in innovative activities with smaller probability, the smaller they are, for those firms that do make such investment, R&D intensity is larger the smaller firms are. For all MSMEs, the predicted R&D intensity is positively correlated with the probability of reporting innovation, with a larger effect size for product than for process innovations. Moreover, micro firms benefit in a comparable way from innovation processes as larger firms, as they are similarly able to increase their labor productivity. Overall, the link between R&D, innovation, and productivity in micro firms does not largely differ from their larger counterparts.
Keywords: L25; L60; O31; O33; 330; MSMEs; micro firms; small firms; R&D; innovation; productivity